Ion mobility-based sterolomics reveals spatially and temporally distinctive sterol lipids in the mouse brain - Tongzhou Li (Nature Portfolio, 2021)
Sterol lipids are crucial for maintaining proper brain function. Here, the authors combine ion mobility-mass spectrometry and machine learning to assemble a sterol lipid library and characterize differences in sterol lipids across ten brain regions and two age groups in mice.